Kajian Kebutuhan Air Irigasi Pada Daerah Irigasi Tawangsari, Kabupaten Jombang - Ramadhani, Safira; Rosytha, Anna; Huda, Miftachul (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2019)
Water is very important for the survival of living things in this world. Therefore there needs to be a balance between the needs and availability of water, including the need for water in agricultural areas. Water requirements in agricultural areas such as Tawangsari irrigation areas, especially paddy fields, are influenced by several factors, namely; Evapotranspiration, layer replacement, and effective rainfall. The availability of Tawangsari irrigation water from the very limited Tawangsari Dam is a major problem in the Tawangsari irrigation area. From the above problems, it is necessary to study the efficiency of water requirements in the irrigation area by analyzing effective rain, irrigation water needs and the availability of irrigation water. The analysis referred to the Irrigation Planning Criteria 01. From the results of the analysis it could be concluded that the water discharge was very sufficient and could be used to irrigate new land, while the calculation of the amount of water needs was greater than the water available in the dry season. Then from that another alternative was needed, namely by a water distribution rotation system and replacement of the water layer according to the available water so that the available water discharge could be sufficient for the needs.